2013
DOI: 10.1016/j.rmed.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Can exhaled nitric oxide differentiate causes of pulmonary fibrosis?

Abstract: FENO could be a tool for differentiating chronic HP from other types of pulmonary fibrosis. The mechanism involved seems to be bronchiolar disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 33 publications
4
23
1
1
Order By: Relevance
“…Tiev et al (2013) obtained similar results to ours in a very recent study of a population of patients with pulmonary fibrosis associated with systemic sclerosis, in whom increased Calv NO in exhaled breath was associated with severe reduction in TLC and TLCO. Although FeNO at 50 ml/s is recognized as a central airways parameter, its elevation in IPF patients has also been reported by Guilleminault et al (2013), with values comparable to ours, suggesting that elevated alveolar concentrations of NO could drive the increased levels measured at all flow rates.…”
Section: No and Lung Function Testssupporting
confidence: 90%
“…Tiev et al (2013) obtained similar results to ours in a very recent study of a population of patients with pulmonary fibrosis associated with systemic sclerosis, in whom increased Calv NO in exhaled breath was associated with severe reduction in TLC and TLCO. Although FeNO at 50 ml/s is recognized as a central airways parameter, its elevation in IPF patients has also been reported by Guilleminault et al (2013), with values comparable to ours, suggesting that elevated alveolar concentrations of NO could drive the increased levels measured at all flow rates.…”
Section: No and Lung Function Testssupporting
confidence: 90%
“…The HRCT findings that best differentiate chronic HP from NSIP and IPF include the presence of lobular areas with decreased attenuation and vascularity, centrilobular nodules, and lack of lower zone predominance of abnormalities . Interestingly, it has been recently suggested that high FeNO levels could help to differentiate chronic HP from other types of pulmonary fibrosis . HP should also be considered in patients diagnosed with NSIP, as a NSIP pattern without granulomas can be the only pathologic finding of HP .…”
Section: Diagnosismentioning
confidence: 99%
“…At baseline, none of our patients had FE NO >40 ppb, which is proposed as a cut‐off point to detect chronic HP, and FE NO did not decrease with treatment. Thus, FE NO measurements do not appear to have clinical utility for diagnosis or follow‐up in cases of chronic HP.…”
Section: Discussionmentioning
confidence: 71%
“…26 After treatment, about 40% of our patients exceeded the minimal, clinically significant difference of 30 m in the 6MWD proposed for patients with idiopathic pulmonary fibrosis. 31 At baseline, none of our patients had FE NO >40 ppb, which is proposed as a cut-off point to detect chronic HP, 32 and FE NO did not decrease with treatment. Thus, FE NO measurements do not appear to have clinical utility for diagnosis or follow-up in cases of chronic HP.…”
Section: Demonstrated Thatmentioning
confidence: 75%